Performa Tanaman Kelapa Sawit pada Musim Kering di Sumatera Selatan: Pengaruh Pemupukan terhadap Pertumbuhan Vegetatif dan Status Hara Tanaman - Didik Wahyu Prasetyo; M. Nur Fanani Kramajaya; Ruli Wandri; Dwi Asmono (Seminar Nasional Lahan Suboptimal, 2018)
Prasetyo et al, 2019. Performance of Palm Oil in Dry Season in South Sumatera: Effect of Fertilizer on Vegetative Growth and Status of Nutrient. pp. 60-66.Most of the oil palm plantations in South Sumatra Province are planted in acid soils (Ultisol and Oxisol). The main limiting factor in acid soils is high acidity with low fertility. This condition is coupled with the typical climate conditions in South Sumatra, namely the existence of a strict boundary between the rainy and dry seasons. When the dry season, it is not uncommon to find water deficits. This study was conducted to determine the relationship between water deficit events and vegetative growth and nutrient content of oil palm. This study was carried out by exploiting data in fertilization experiments. Fertilization experiments using factorial design N3P2K3Mg2 (higher order partially confounded interactions) and each plot consisted of 64 trees. The results of the study showed that in general the water deficit events in 2014 decreased 4-6 frond per year in the same year and decreased 2-6 frond per year in 2015. Increased K content in the leaves will increase frond production. The optimum K content to maintain a fixed 24 frond production is 1.1%. This study can be used as initial information for management of fertilization management in the event of a water deficit.